Computational Linguistics Models and Language Technologies for Indonesian - Dian Noviani Syafar; Ria Febrina (Masyarakat Linguistik Indonesia Universitas Andalas, 2019)
The purpose of this research is to describe computational linguistics as a study of science that should pay full attention to linguistics researches improvement. The type of research is a literature review and experimental research by designing a software model for Bahasa. The result of the research shows that computational linguistics is a field of linguistics that can be used as a solution to overcome a problem related to spelling correction and grammar for language users. This field of linguistics is related to software engineering designed to educate the public in producing languages; it can be Bahasa, regional language, and English language as the foreign language for Indonesian. The public can know the standardization of writing a language and equivalence translation between the target language and the source language that can also be precisely acquired. Also, the writer provides several practical examples of how computational linguistics can be applied to the development of writing skills. For instance, the concordance enables us to see any word or phrase in context so that one can see what sort of company it keeps. Thus, the users can, for example, see the correct form based on Bahasa Indonesia rules between the words which they often confuse (e.g., gadget vs. gawai).